Staphylococcus aureus β-Hemolysin Up-Regulates the Expression of IFN-γ by Human CD56bright NK Cells - Guan, Zhangchun; Liu, Yu; Liu, Chenghua; Wang, Huiting; Feng, Jiannan; Yang, Guang (Frontiers in Cellular and Infection Microbiology, 2021)
IFN-γ is produced upon stimulation with S. aureus and may play a detrimental role during infection. However, whether hemolysins play a role in the mechanism of IFN-γ production has not been fully characterized. In this study, we demonstrated that Hlb, one of the major hemolysins of S. aureus, upregulated IFN-γ production by CD56bright NK cells from human peripheral blood mononuclear cells (PBMCs). Further investigation showed that Hlb increased calcium influx and induced phosphorylation of ERK1/2. Either blocking calcium or specifically inhibiting phosphorylation of ERK1/2 decreased the production of IFN-γ induced by Hlb. Moreover, we found that this process was dependent on the sphingomyelinase activity of Hlb. Our findings revealed a novel mechanism of IFN-γ production in NK cells induced by Hlb, which may be involved in the pathogenesis of S. aureus.